Testing the Differential Impact of COVID-19 on Self-Employed Women and Men in the United Kingdom - Darja Reuschke; Andrew Henley; Elizabeth Daniel; Victoria Price (Institute of Labor Economics (IZA), 2021)
This paper investigates whether the female self-employed are more affected by the COVID-19 crisis than the male self-employed using longitudinal data four months following the first 'lockdown' in the UK. We specifically test the role of family/social, economic and psychological factors on gendered differential impact. We find that self-employment exits are not gendered but women are more likely to experience reductions in hours worked and earnings. This greater adverse impact on women's working hours and earnings is despite family responsibilities and home-schooling, industrial gender segregation and women's greater propensity to run a non-employing business and to work part-time. However, lower attitude to risk in women is associated with lower risk of reduction in earnings. Policy needs to look beyond business exits when considering crisis support for the self-employed.
Keywords: J16; J22; L26; 330; entrepreneurship; self-employment; COVID-19; gender; labour supply